The effect of extruder pressure of 3D bioprinter on hardness and compressive of scaffold bovine hydroxyapatite. Issue 1 (1st January 2019) - Triyono, Joko; Nurzengky, Ahlan; Sukanto, Heru; Nugroho, Yohanes
Abstract: The aims of the study are to find out bio-printer extruder pressure effect toward the hardness and compressive strength of bovine hydroxyapatite (BHA). BHA and Glycerin are mixed with a 1:1 ratio. After 24 h bioink will be formed and can be used as a material to print scaffold. The scaffold is printed with a pressure variation of 100, 150, 200 and 250 KPa. After the printing process is done, the scaffold is kept on heat bed for 10 min with 100°C temperature. The hardness test result in this study has the highest value of 24.23 ± 1.22 HVN and 2.03 ± 0.12 HVN for its lowest. The compressive strength test has the highest value of 5.71 ± 0.42 MPa with the lowest value of 3.22 ± 0.13 MPa. The observation of BHA scaffold pores using a microscope shows that the pores have an average size of 100–200 µm.